Dragão de luz: uma poética sobre a experimentação de iluminação cênica do espetáculo santo anjo do senhor - LISBOA, Marckson Davi de Moraes (Universidade Federal do Pará, 2019)
This research deals with spectacle’s light trials of Santo Anjo do Senhor, from Companhia Cênica de Cínicos of Belém of Pará. As an artist-illuminator-researcher, I seek to investigate the potential of non-theatrical equipment, devices and lighting materials, and the interaction of these scenic resources with the actor and the space within an experimental staging. The research develops by Gaston Bachelard's Phenomenology of Imagination to analyze the light of the spectacle as a phenomenon through the bias of daydream. For this, I summon Gilbert Durand’s imaginary conception, the Antonin Artaud’s scenic proposal, provocations of Eugenio Barba, propositions of Patrice Pavis and perceptions of scenic lighting of Roberto Gil Camargo, Cibele Forjaz, Francisco Turbiani e Iara Souza, further, explanations of Cecilia Salles and Sonia Rangel on creation processes to compose a methodology based on the Dragon myth, as poetic image. In the research, I visit both Chinese mythology and the imagery poetry of the tale Os dragões não conhecem o paraíso by Caio Fernando Abreu, to approach the development of scenic lighting over four-year seasons of the spectacle.